Deleterious effects of phosphatidylethanolamine plasmalogen oxidation via singlet molecular oxygen - Faria, Rodrigo Lucas de (2023)
Plasmalogens are phospholipids present in all human tissues. They represent about 20% of all phospholipids. They are characterized by the presence of a vinyl ether-type bond in the aliphatic chain at the sn-1 position of glycerol, while at the sn-2 position of glycerol it is esterified, in most cases, to polyunsaturated fatty acids (PUFAs). Although studies have demonstrated the protective effects of plasmalogens in cellular models subjected to oxidative stress, the proposed mechanisms for their antioxidant effect are controversial. For example, the reaction of the vinyl ether group with reactive oxygen species (ROS) generates reactive products such as dioxetanes and aldehydes, which can propagate oxidative damage. Electron-rich groups, such as the vinyl ether of plasmalogens, form dioxetane with singlet oxygen by a (2+2) cycle addition reaction. Dioxetans are generally unstable and decompose rapidly by thermolysis, generating excited carbonyl. This excited species can decay to the ground state by emitting visible light, but it can also transfer energy to molecular oxygen in the ground state (O2(3&#916g-)), thus producing singlet molecular oxygen (O2(1Δg))11. This process of O2(1&#916g) formation is called photochemistry in the dark. Furthermore, lipid hydroperoxides in the presence of oxidizing ions, such as iron 2+, can also generate O2(1&#916g) by Russell mechanism. Therefore, plasmalogen oxidation via O2(1&#916g) can propagate oxidation reactions by photochemistry in the dark and Russel mechanism. To test this hypothesis, the present study aims to: a) perform a qualitative and quantitative oxylipidomics analysis (lipidomics of non-oxidized and oxidized lipids) focusing on lipid remodeling induced by oxidation via singlet oxygen generated by photooxidation in HaCat keratinocytes, b) characterize the main oxidized products (dioxetanes, aldehydes, lysophospholipids, etc.) derived from the reaction of plasmalogen with singlet oxygen, c) study the mechanisms of plasmalogen oxidation and the effects of plasmalogen oxidation on models of membranes and cells, d) Analysis of free fatty acids by UPLC-Fluorescence, as there is great interest in knowing the composition of fatty acids in biological samples, as changes in these lipids are associated with pathological conditions, in addition to being precursors of signals such as prostaglandin.